Morphologie urbaine et mobilité en marche à pied - Cyrille Genre-Grandpierre (Unité Mixte de Recherche 8504 Géographie-cités, 2003)
The aim of this paper is to better understand the decisive factors of the daily walking practices in urban areas. It is based on the hypothesis that the urban morphology determines partially the walking practices by producing the quality of the pedestrian accessibility. The test of this hypothesis uses original data for Besançon and Lille. These data, describing walking practices, including the itineraries, have been collected through two telephone surveys and implemented in a Geographical Information System. According to our work hypothesis, it turns out that high accessibility for pedestrians from their homes tends to promote the use of walking. The analysis of the travels which could be done on foot, but which are actually done by an other mean of transportation, confirms the role of the structure: it shows that the efficiency of the street network influences the walking practices, particularly the modal choice. Besides, the level of pedestrian traffic, either local or transit, turns out to depend partly on the quality of the local pedestrian accessibility, all the more because the urban structure is organised around a single centre. Finally, among the geometrical criteria of the ground occupation likely to account to the pedestrian traffic, the spatial fragmentation appears to be an influential variable to emphasise the use of walking.